2010
DOI: 10.1111/j.1523-1739.2010.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Approach to Conserving Amazonian Biodiversity

Abstract: Amazonia is a highly threatened rainforest that encompasses a major proportion of Earth's biological diversity. Our main goal was to establish conservation priorities for Amazonia's areas of endemism on the basis of measures of evolutionary distinctiveness. We considered two previously identified sets of areas of endemism. The first set consisted of eight large areas used traditionally in biogeographical studies: Belém, Tapajós, Xingu, Guiana, Rondônia, Imeri, Inambari, and Napo. The second set consisted of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…7 ). These results are similar to those found by López-Osorio and Miranda-Esquivel ( 2010 ). Here the re-sampling helped to resolve the initial discrepancy as the highest priority is Guiana2 and not Rondonia, that could be a possible candidate.…”
Section: Second Case: the Support For The Original Rankingsupporting
confidence: 80%
See 2 more Smart Citations
“…7 ). These results are similar to those found by López-Osorio and Miranda-Esquivel ( 2010 ). Here the re-sampling helped to resolve the initial discrepancy as the highest priority is Guiana2 and not Rondonia, that could be a possible candidate.…”
Section: Second Case: the Support For The Original Rankingsupporting
confidence: 80%
“…and given that index, which are the areas chosen as the fi rst and second priority?. López-Osorio and Miranda-Esquivel ( 2010 ) found that most indices selected the same area Guiana2, which could be seen as there is no difference given the index. The reanalysis showed that in general I s and W s are more stable than any other index, and I s behaves better than W s .…”
Section: Second Case: the Support For The Original Rankingmentioning
confidence: 84%
See 1 more Smart Citation
“…This book is organized around three main themes: questions, methods and applications. We hope that this concentrated effort will contribute to Vane-Wright et al 1991 ;May 1990 ;Faith 1992 ;Posadas et al 2001 ;Pavoine et al 2005 ;Redding and Mooers 2006 ;Isaac et al 2007 ;Steel et al 2007 ;Hartmann and Steel 2007 ;Lozupone and Knight 2005 ;Rosauer et al 2009 ;Cadotte and Davies 2010 ;Chao et al 2010 Comparison of phylogenetic measures Schweiger et al 2008 ;Davies and Cadotte 2011 ;Pio et al 2011 Comparison of phylogenetic diversity to traditional measures Polasky et al 2002 ;Rodrigues and Gaston 2002 ;Rodrigues et al 2005Rodrigues et al , 2011Hartmann and André 2013 Inclusion of phylogenetics in systematic conservation planning Walker and Faith 1994 ;Arponen 2012 Prioritization of areas for the conservation of evolutionary history Posadas et al 2001 ;Lehman 2006 ;McGoogan et al 2007 ;López-Osorio and Miranda-Esquivel 2010 ;Forest et al 2007 ;Buerki et al 2015 ;Pollock et al 2015 ;Zupan et al 2014 Prioritization of species Weitzman 1998 ;Isaac et al 2007 ;Kuntner et al 2011 ;Redding et al 2015 Relationship between extinctions and the loss of phylogenetic diversity Nee and May 1997 ;Purvis 2008 ;…”
Section: Glossarymentioning
confidence: 99%
“…Although the possibility of integrating results from different phylogenies has been studied for a while (see Posadas et al 2001Posadas et al , 2004Faith et al 2004 ;López-Osorio and Miranda Esquivel 2010 ), we are only starting to explore the implications of different sampling effort and imperfect knowledge on studies of phylogenetic diversity for assessing areas for conservation (see Nipperess and Matsen 2013 and Nipperess, chapter " The Rarefaction of Phylogenetic Diversity : Formulation, Extension and Application " and Miranda-Esquivel, chapter " Support in Area Prioritization Using Phylogenetic Information "). In order to shed light to this problem here we propose some solutions when assessing hotspots for conservation within New Caledonia .…”
Section: Introductionmentioning
confidence: 99%